ANALISIS KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL UJIAN NASIONAL MATEMATIKA SMP/MTs BERDASARKAN PERSPEKTIF HIGHER ORDER THINKING SKILLS (HOTS) - Deda, Yohanis Ndapa; Ratu, Astry H; Amsikan, Stanislaus; Mamoh, Oktovianus (Jurnal Pendidikan Matematika (JUPITEK), 2020)
This study aims to analyze the ability of mathematics junior high school students in resolving the mathematics HOTS in the national exam (UN). The methodology used is a descriptive qualitative study. The subject of study is six students of ninth grade consisting of two capable, two people are low capacity, and two others high-profile. Data collection in this research using interviews and test one package the exam every year from 2016-2018, then been validated by the expert, who is elected seven items of about which include an item in 2016, two items of the year 2017, and four items of the year 2018. An instrument used is an enlightenment interview and the national exam in HOTS categorize. The result showed that students low capable with only able to solve the item number-1 and number-4 wich including in HOTS level-4 and 5, and students who are capable of being able to solve problems HOTS have similarities with students who are highly capable of being able to solve the questions number 1, 2, 3, 4, and 7 with HOTS levels 4, 5, and 6